2021
DOI: 10.1371/journal.ppat.1009682
|View full text |Cite
|
Sign up to set email alerts
|

Development of emodepside as a possible adulticidal treatment for human onchocerciasis—The fruit of a successful industrial–academic collaboration

Abstract: Current mass drug administration (MDA) programs for the treatment of human river blindness (onchocerciasis) caused by the filarial worm Onchocerca volvulus rely on ivermectin, an anthelmintic originally developed for animal health. These treatments are primarily directed against migrating microfilariae and also suppress fecundity for several months, but fail to eliminate adult O. volvulus. Therefore, elimination programs need time frames of decades, well exceeding the life span of adult worms. The situation is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…Expert consultations and detailed analyses of available data spearheaded by APOC concluded that alternative treatment strategies (ATS), including those with more effective drugs than ivermectin, are needed to eliminate parasite transmission in many areas [ 22 ]. Research into different types of ATS [ 23 ] is ongoing, including discovery and development of more effective drugs [ 24 26 ], identification of effective, affordable, and sustainable complementary vector control strategies [ 27 ] and studies for implementation of new ‘test-and-not-treat’ or ‘test-and-treat’ strategies for Loa-loa co-endemic areas [ 28 32 ]. Furthermore, research for a vaccine is continuing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expert consultations and detailed analyses of available data spearheaded by APOC concluded that alternative treatment strategies (ATS), including those with more effective drugs than ivermectin, are needed to eliminate parasite transmission in many areas [ 22 ]. Research into different types of ATS [ 23 ] is ongoing, including discovery and development of more effective drugs [ 24 26 ], identification of effective, affordable, and sustainable complementary vector control strategies [ 27 ] and studies for implementation of new ‘test-and-not-treat’ or ‘test-and-treat’ strategies for Loa-loa co-endemic areas [ 28 32 ]. Furthermore, research for a vaccine is continuing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bma-glc-3 and Bma-glc-4 channel subunits are more enriched in the head and may also play a role in macrocyclic lactone responses. Bma-slo-1 , a putative target of emodepside, an emerging candidate adulticide for treatment of river blindness [ 38 ], is more highly expressed in the body. Conversely, the likely β-tubulin target of albendazole ( Bma-btub-1 ), based on homology to Caenorhabditis elegans ben-1 , is head-enriched.…”
Section: Resultsmentioning
confidence: 99%
“…In general, adoptive transfer experiments using RAG2IL-2Rγ-deficient C57BL/6 mice provide an optimal platform to decipher cell subsets and their corresponding immune responses that are crucial for anti-filarial immunity. Since our recent studies already showed that RAG2IL-2Rγ-deficient C57BL/6 mice are susceptible to the human filaria Loa loa ( 35 , 66 , 74 ), this platform is not restricted to rodent filariae but will also be a suitable tool for in-depth research on human filariae and preclinical research, especially might allow the identification of essential immunological component(s) and accurate predictions of the efficacy of macrofilaricidal drugs, like flubendazole ( 75 ), oxfendazole ( 76 ) or emodepside ( 77 ).…”
Section: Discussionmentioning
confidence: 99%